2020
DOI: 10.1111/jvp.12918
|View full text |Cite
|
Sign up to set email alerts
|

Sulfadiazine pharmacokinetics in grass carp (Ctenopharyngodon idellus) receiving oral and intravenous administrations

Abstract: This study aimed to examine the bioavailability (BA) and pharmacokinetic (PK) characteristics of sulfadiazine (SDZ) in grass carp (Ctenopharyngodon idellus) after oral and intravenous administrations. Blood samples were collected at predetermined time points of 0.083, 0.17, 0.5, 1, 2, 4, 8, 16, 24, 48, 72, and 96 hr (n = 6). The samples were extracted and purified by organic reagents and determined by the ultra‐performance liquid chromatography. The software named 3P97 was used to calculate relevant PK paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…It has been reported that the absorption and excretion rate of compounds in fish that have a stomach is faster than the fish that do not have a stomach (Takii et al, 1997). Under the same experimental conditions, the t 1/2Kα of channel catfish is shorter than that of grass carp, which just proved the conclusion from the literature (Xu et al, 2020). However, t 1/2Kα values of tilapia and mandarin fish are longer than that of grass carp, which may be attributed to different dosages and environmental temperatures.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It has been reported that the absorption and excretion rate of compounds in fish that have a stomach is faster than the fish that do not have a stomach (Takii et al, 1997). Under the same experimental conditions, the t 1/2Kα of channel catfish is shorter than that of grass carp, which just proved the conclusion from the literature (Xu et al, 2020). However, t 1/2Kα values of tilapia and mandarin fish are longer than that of grass carp, which may be attributed to different dosages and environmental temperatures.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, the t 1/2Kα value (0.87 h) in channel catfish was shorter than that in grass carp (2.29 h) under the same oral dosage of 50 mg/kg at an environment temperature of 24℃ (Xu et al, 2020). It is also shorter than the t 1/2Kα values of 5.27 h in tilapia ( Oreochromis niloticus ) after oral administration of compound SDZ (m‐SDZ: m‐trimethoprim = 1:5, 120 mg/kg) at 23℃ (Xiao et al, 2014) and 5.7 h in mandarin fish ( Siniperca chuatsi ) after oral administration of compound SDZ at 28℃ (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 52%
“…Many published references have proved this phenomenon such as florfenicol (Rairat et al, 2019; Yang et al, 2018, 2019), doxycycline (Xu et al, 2019), oxolinic acid (Rigos et al, 2002b), oxytetracycline (Rigos et al, 2002a; Rosa et al, 2019), and flumequine (Sohlberg et al, 1994). Recently, we examined the bioavailability of SDZ in grass carp and channel catfish (Xu, Fu, et al, 2021, 2022), and the pharmacokinetics of SDZ in grass carp at different temperatures (Xu, Li, et al, 2022). To our knowledge, there is no report about the influence of environmental temperature on SDZ pharmacokinetics in channel catfish.…”
Section: Introductionmentioning
confidence: 99%